2010
DOI: 10.4067/s0717-97072010000400018
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of New Optically Active and Thermally Stable Poly(amide-Imide) Containing Bicyclo Segment and Ether Group in the Main Chain by Direct Polycondensation in Two Different Media

Abstract: A new series of optically active and thermally stable poly(amide-imide)s (PAIs) with good inherent viscosities based on bicyclo diacids and etheric diamine in the main chain were synthesized from the direct polycondensation reaction of N, N΄-(bicyclo[2,2,2]oct-7-ene-tetracarboxylic)-bis-l-amino acids 3a-g with 1,2-Bis[4-aminophenoxy]ethane 7 by direct polycondensatios with two different media such as direct polycondensation in a medium consisting of n-methyl-2-pyrrolidone (NMP)/triphenyl phosphite (TPP)/calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…We recorded nuclear magnetic resonance (NMR), Fourier transform infrared (FTIR), and XPS spectra to confirm the structures of our PDs. A comparison of the 1 H NMR spectra of BCDA, EDTAD, Jeffamine T-403, and the PDs revealed that only those of the PDs featured signals at 7.94 ppm, representing the H atoms of their amido groups (Figure a–e). Figure S3a displays the FTIR spectra of BCDA and EDTAD, featuring signals for the symmetric and asymmetric stretching of their CO units in the ranges 1761–1774 and 1809–1822 cm –1 , respectively. , After the dianhydrides had reacted with the triamine to form poly­(amic acid)­s with amido and carboxyl groups, Figure S3b reveals that the FTIR spectra of PD-BT-12 and PD-ET-12 lacked any signals for symmetric and asymmetric stretching of the CO units of the dianhydride but signals had emerged for amide I and II vibrational modes in the ranges 1543–1560 and 1657–1663 cm –1 , respectively …”
Section: Resultsmentioning
confidence: 99%
“…We recorded nuclear magnetic resonance (NMR), Fourier transform infrared (FTIR), and XPS spectra to confirm the structures of our PDs. A comparison of the 1 H NMR spectra of BCDA, EDTAD, Jeffamine T-403, and the PDs revealed that only those of the PDs featured signals at 7.94 ppm, representing the H atoms of their amido groups (Figure a–e). Figure S3a displays the FTIR spectra of BCDA and EDTAD, featuring signals for the symmetric and asymmetric stretching of their CO units in the ranges 1761–1774 and 1809–1822 cm –1 , respectively. , After the dianhydrides had reacted with the triamine to form poly­(amic acid)­s with amido and carboxyl groups, Figure S3b reveals that the FTIR spectra of PD-BT-12 and PD-ET-12 lacked any signals for symmetric and asymmetric stretching of the CO units of the dianhydride but signals had emerged for amide I and II vibrational modes in the ranges 1543–1560 and 1657–1663 cm –1 , respectively …”
Section: Resultsmentioning
confidence: 99%